MYH9 Aggregation Induced by Direct Interaction With PRRSV GP5 Ectodomain Facilitates Viral Internalization by Permissive Cells - Xue, Biyun; Hou, Gaopeng; Zhang, Guixi; Huang, Jingjing; Li, Liangliang; Nan, Yuchen; Mu, Yang; Wang, Lizhen; Zhang, Lu; Han, Ximeng; Ren, Xiaolei; Zhao, Qin; et al. (Frontiers in Microbiology, 2019)
Prevention and control of infection by porcine reproductive and respiratory syndrome virus (PRRSV) remains a challenge, due to our limited understanding of the PRRSV invasion mechanism. Our previous study has shown that PRRSV glycoprotein GP5 interacts with MYH9 C-terminal domain protein (PRA). Here we defined that the first ectodomain of GP5 (GP5-ecto-1) directly interacted with PRA and this interaction triggered PRA and endogenous MYH9 to form filament assembly. More importantly, MYH9 filament assembly was also formed in GP5-ecto-1-transfected MARC-145 cells. Notably, PRRSV infection of MARC-145 cells and porcine alveolar macrophages also induced endogenous MYH9 aggregation and polymerization that were required for subsequent PRRSV internalization. Moreover, overexpression of S100A4, a MYH9-specific disassembly inducer, in MARC-145 cells significantly resulted in diminished MYH9 aggregation and marked inhibition of subsequent virion internalization and infection by both PRRSV-1 and PRRSV-2 isolates. The collective results of this work reveal a novel molecular mechanism employed by MYH9 that helps PRRSV gain entry into permissive cells.